Effects of Short Video Addiction on the Motivation and Well-Being of Chinese Vocational College Students - Ye, Jian-Hong; Wu, Yu-Tai; Wu, Yu-Feng; Chen, Mei-Yen; Ye, Jhen-Ni (Frontiers in Public Health, 2022)
With the popularity of the Internet, students’ online addiction is generally considered to have a serious impact on the quality and outcomes of their learning, resulting in the ongoing concern and discussion of online addictive behaviors among educators around the world. Among other things, the problem of online addiction among Chinese youth has led the government to propose a series of control policies to strengthen the monitoring of harmful habits of youth in the use of online applications, thus demonstrating that online addiction is indeed an ongoing research issue. With the popularity of Chinese video applications (apps) such as DouYin, TikTok, Kwai and other short video apps sweeping through schools around the world, the problem of youth addiction to short videos has become a major concern for education experts and the general public. Therefore, this study aimed to understand the causes of short-form video addiction and its impact on the psychology of learning, and to investigate the relationship between short-form video flow experience, short-form video addiction, intrinsic and extrinsic learning motivation, and learning well-being from the perspectives of flow experience theory and micro ecological systems. The questionnaire was sent via instant messaging software such as QQ and WeChat, and university students from vocational colleges in China were invited to complete the questionnaire. The collected questionnaires were analyzed for reliability and validity after removing incomplete data, followed by structural equation modeling for model verification. The findings showed that: 1. Short video flow experience had a positive effect on short video addiction; 2. Short video addiction had a negative effect on intrinsic and extrinsic learning motivation; 3. Intrinsic and extrinsic learning motivation had a positive effect on learning well-being; 4. Short video flow experience had an indirect negative effect on intrinsic and extrinsic learning motivation; 5. Short video flow and short video addiction had indirect negative effects on learning well-being. According to the results, it is clear that addiction to short videos has a negative impact on learners’ learning motivation and positive psychology of learning, so parents and teachers should effectively guide students to use short video apps in a self-controlled way.